Let's stop calling it an achievement gap : how public education in the United States maintains disparate educational experiences for students of color - Arnett, Autumn A. (Contemporary perspectives on access, equity, and achievement., 2019)
"Between 1980 and 2005, 45 states were involved in lawsuits around equity of funding and adequacy of education provided to all students in the state. Indeed, this investigation could have included any cities in America, and the themes likely would have been the same: Lower funding and resources, disproportionate numbers of teachers and school leaders who do not look like the students they serve, debates over the public's responsibility to provide fair and equitable education for all students in the jurisdiction, implicit biases from the top to the bottom and a resegregation of schools in America. Integration for Black families was never about an idea that Black students were better off if they could be around White students, it was about the idea that Black students would be better off if they could have access to the same education that white students had -- but residential segregation still enables de facto school segregation, when it isn't coded into policy. But for the overwhelming majority of Black students, they're stuck in segregated, underperforming schools. Schools where the teachers are dedicated to the mission, but where the cities and districts and states have failed to uphold their basic responsibility to maintain the upkeep of the schools and provide enough desks for each child and current textbooks"--